(untitled) (Politeja, 2016)
Where the Iron Curtain fell? Borders and the myth of Central Europe in contemporary essays and European historiography The present paper discusses the key writer’s views of the Central Europe, referring to the problem of the symbolic divisions of Europe in opinion journalism and essays. It presents three main ways (cultural, political and social) of constructing the borders of Central Europe, and thus of Europe’s eastern border. The author focuses primarily on those publications in which the authors propose a redefinition of borders in Central Europe. She refers, amongst others, to the texts of Milan Kundera, Chantal Delsol, Alain Finkielkraut, Simona Škrabec, Vittorio Strada, Andrzej Stasiuk, and Yuri Andrukhovych. She also describe and deconstructs the myth of “unique geographical location which shaping the identity of Central Europe”, emerging from the texts of the writers mentioned above.